Fenomena Penggunaan ChatGPT sebagai Media Konsultasi Mahasiswa dalam Mengekspresikan Diri - Ayu Amalia Makatita; M Iqbal Husein (GLOBAL SCIENTS PUBLISHER, 2026)
The use of ChatGPT as a consultation tool has grown among university students, especially when face-to-face communication is uncomfortable due to concerns about judgment. This study aims to explore how Communication students at Pattimura University, class of 2022, utilize ChatGPT to express themselves on personal and emotional issues, using the hyperpersonal model as the conceptual framework. A descriptive qualitative approach was employed, with in-depth interviews focusing on communication patterns and students subjective experiences. Findings indicate that ChatGPT is perceived as neutral, responsive, and non-judgmental, fostering openness, a sense of security, and the ability to assess issues more clearly. Repeated interactions further enhance an intensive and reflective communication experience. These findings contribute to the field of Communication by highlighting shifts in students’ interpersonal communication patterns and demonstrating the potential of artificial intelligence as a medium for self-expression in digital communication.